Online Assessment on Students’ Writing Recount Text: Teachers’ Perspectives - Dinda Rizkiana; Anni Holila Pulungan (Universitas Negeri Medan, 2023)
This study attempted to investigate what were the kinds of online assessment for students writing recount text used by the teachers and to analyze how were the teachers’ perspectives on the online assessment on students’ writing recount text. A descriptive qualitative design was used in this study. The data were collected by doing deep interview with two English teachers of SMA Negeri 6 Medan. The result of this study found that the teachers used Google Classroom as the online assessment. And based on the theory of Remmi (2020), the teachers’ have two perspectives on the online assessment, namely: affordances and constraints. Furthermore, the teachers faced some obstacles while conducting the online assessment, namely: unstable internet connection, lack of facilities, and lack of skills. Meanwhile for the affordances, the teachers stated that online assessment was easy to use and improve teaching practice. Regarding to those findings, the teachers’ perspective on the online assessment on students’ writing recount text in SMA Negeri 6 Medan were categorized into constraints.Keywords: Online Assessment, Teachers’ Perspective, Recount Text